Pengaruh Pemasaran Dalam Jaringan pada Usaha Mikro Kecil Menengah (UMKM) di Kota Yogyakarta - Agustina, Era; Musoli, Musoli (Politeknik Negeri Ambon, 2024)
This study is aim to determine and examine the effect of online marketing on the small bussines in city of Yogyakarta. Social media and e-commerce platforms are the online marketing media focused on this research. This study uses quantitative methods with a questionnaire as a data collection tool with qualitative data support to enrich quantitative data. Respondents in this study were small bussines practitioners with a sample of small bussines factors in city of Yogyakarta. Data analysis in this study used the Structural Equation Model (SEM). A pilot study was conducted first in this study to test the validity and reliability of the statement items on the questionnaire used in this study. The output of this research is expected to be additional reference material both in the academic field, especially marketing management regarding online marketing. As for the practical output of this study, it is hoped that it can become a material for consideration and reference for small bussines practitioners on city of Yogyakarta in particular, and in Indonesia in general in an effort to increase their income and maintain their business continuity. The results of this study indicate the influence of sales through social media and electronic trading platforms on the income of small bussines in the city of Yogyakartka.